Overview of Adolescent Knowledge Level About Healthy Eating as Early Detection of Metabolic Syndrome at Saraswati 1 Denpasar High School (SLUA) - Triyuliani, Ni Komang; Anita Pramesti, Theresia; Intan Saraswati, Ni Luh Gede (Future Science, 2025)
Introduction: Metabolic syndrome is identified as one of the global health problems that could increase the risk of non-communicable diseases such as diabetes mellitus, hypertension, and cardiovascular disease. In adolescents, an unhealthy diet is recognized as one of the main triggering factors for metabolic syndrome, making preventive efforts necessary through the enhancement of knowledge about healthy eating. Objective: This study aimed to describe the level of adolescent knowledge about healthy eating as an early detection of metabolic syndrome at Saraswati 1 Denpasar High School (SLUA). Methods: The research utilized a quantitative descriptive design with a multistage random sampling technique and involved 283 samples. Data were collected using questionnaires that had been tested for validity and reliability. Results: The results indicated that the majority of respondents had a good level of knowledge about healthy eating. The crosstabulation analysis revealed that respondents with a good level of knowledge were mainly 16 years old, female (58.0%), had a normal BMI (59.2%), no family history of illness (52.4%), and had received counseling (57.1%). The majority of adolescents' knowledge levels were lowest in the healthy eating indicator, with 155 individuals (54.8%), and highest in the eating schedule indicator, with 248 individuals (87.6%). The good knowledge level among respondents related to healthy eating was influenced by several factors, including sufficient information exposure and educational programs provided through school health education. Conclusion: Adolescents is advised to manage their diet according to the 3J principle (schedule, type, and amount of food) and to be more selective in their food consumption.